Factors influencing customer Loyalty on Perusahaan Otomobil Kedua Sdn Bhd (Perodua) products / Ahmad Hafiz Azizan - Azizan, Ahmad Hafiz (Faculty of Business and Management, 2007)
In recent years, Perusahaan Otomobil Kedua Sdn Bhd (PERODUA) had achieved great success in the local automobile industry by receiving many awards and acknowledgements in local and international automotive industry. For the first time, monthly sales of Perodua passenger cars overtook sales of Proton cars. Perodua gained the biggest market share with 27.4% followed closely by Proton at 26.6%. Toyota remained the most popular non-national brand, with 17.4% market share. (AmResearch Sdn Bhd; The Star BizWeek, 1st April 2006).